The Inhibition of Carbon Steel Corrosion in Hydrochloric Acid Media Using 2-((5-methyl-isoxazol-3-yl)-methyl)-benzimidazole - Sebhaoui,J. (2021)
Abstract Carbon steel corrosion inhibition in a hydrochloric acid solution by 2-((5-methyl-isoxazol-3-yl)-methyl)-benzimidazole (MMB) has been studied by electrochemical techniques (PDP and EIS). Results showed that the inhibition efficiency increases with higher MMB concentration, and the maximum value of 86.6% was obtained at 10-3 M concentration. The prepared benzimidazole inhibitor showed higher inhibition efficiency upon raising the solution temperature from 303 to 333 K. Corrosion current density decreased from 660.9 µA cm-2 (blank) to 97.8 µA cm-2 (MMB) and charge transfer resistance increased from 20.2 Ω cm2 (blank) to 150.8 Ω cm2 (MMB). PDP studies showed that MMB is a mixed type inhibitor. The adsorption of this compound onto the carbon steel surface in a 1 M HCl solution followed the Langmuir adsorption isotherm, and the value of the standard free energy of adsorption () is associated to physisorption and chemisorption.